Renewable Energy Consumption in Emerging Countries and Developed Countries - Tiurma Melissa Rakhel (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2020)
Countries require large amounts of energy for continuous economic growth. As mentioned by the US Energy Information Administration, total world energy consumption is expected to increase from 575 quadrillion Btu in 2015 to 736 quadrillion Btu in 2040, or an increase of 28% (U.S. Energy Information Administration (EIA), 2017) . However, resources of non-renewable energy are limited, and energy consumption is known to worsen major environmental problems in the world. To reach a balance between energy needs and environmental problems, using renewable energy is one of the best options for many countries. Given this state of affairs, this study addresses the long-term relationship of renewable energy consumption with respect to output, pollutant emissions and international trade. It uses a panel cointegration technique, along with the Pooled-Mean Group Auto Regressive Distributed Lag (PMG-ARDL) method, to compare a group of emerging countries with a group of developed countries. The study shows that the consumption of renewable energy is positively related to real GDP per capita and international trade for both emerging countries and developed countries, while it is negatively associated with CO2 per capita with a large magnitude. This result suggests that international trade and economic growth will promote the consumption of renewable energy in the long-run future. However, whether an increase in the percentage of renewable energy consumed solves the environmental problems depends a great deal on the future trajectory of CO2 emissions along with economic development. Overall, the empirical analysis in the present study demonstrates that international trade leads to the promotion of the consumption of renewable energy as a long-run relationship. It means that, in the future, economic development along with international trade and advances in environmental technology are expected to further facilitate and promote the consumption of renewable energy in every country. However, governments should issue policies to support significant growth and development of renewable energy along with the economic growth of the country in a manner consistent with the country’s level of development.